Residual pattern of primary tumor and lymph node in ESCC treated with nCRT with or without pembrolizumab: an analysis from a prospective cohort - Han, Xuan; Qi, Wei-Xiang; Li, Shu-Yan; Li, Huan; Chen, Jia-Yi; Zhao, Sheng-Guang (Frontiers in Immunology, 2025)
BackgroundNeoadjuvant chemoradiotherapy (nCRT) is recommended as the standard of care for locally advanced esophageal squamous cell carcinoma (ESCC). Adding immunotherapy to nCRT (nICRT) has gained attention in clinical practice. We evaluated the differences in clinicopathologic outcomes and the patterns of lymph node metastasis in patients receiving nCRT and nICRT for locally advanced ESCC.MethodsA total of 208 ESCC patients who completed transthoracic esophagectomy after neoadjuvant treatment were enrolled. Clinicopathologic parameters and the rates of lymph node metastasis in each station classified using both the eighth edition of the American Joint Committee on Cancer (AJCC) esophageal cancer staging system and the 11th edition of the Japanese Classification of Esophageal Cancer (JCEC) standard were recorded and evaluated.ResultsThe rates of pathological complete response (pCR) and major pathological response (MPR) were 44.9% in nICRT vs. 37.0% in nCRT (p = 0.263) and 79.5% in nICRT vs. 65.4% in nCRT (p = 0.024), respectively. The common sites of lymph node metastasis after neoadjuvant treatment were station 112pulL (8.3%), followed by station 104L (4.9%), station 7 (4.5%), and station 3a (4.3%), according to the 11th JCEC standard. Compared with nCRT, nICRT can significantly reduce the rates of lymph node metastasis in station 2R (0.8% vs. 4.6%, p = 0.039) classified using the AJCC system, and those in station 106recR (0.8% vs. 4.6%, p = 0.042) and station 20 (0 vs. 12.5%, p = 0.030) classified using the JCEC standard.ConclusionnICRT followed by surgery may lead to a promising pathological response. For patients with lymph node metastasis in certain regions, nICRT should be considered as a better preoperative treatment option.